CK2B Induces CD8+ T‐Cell Exhaustion through HDAC8‐Mediated Epigenetic Reprogramming to Limit the Efficacy of Anti‐PD‐1 Therapy in Non‐Small‐Cell Lung Cancer - Shaochuan Liu; Shiya Ma; Gen Liu; Lingjie Hou; Yong Guan; Liang Liu; Yuan Meng; Wenwen Yu; Ting Liu; Li Zhou; Zhiyong Yuan; Shuju Pang; et al. (Advanced Science)
Abstract Anti‐PD‐1 therapy has left an indelible mark in the field of non‐small‐cell lung cancer (NSCLC) treatment; however, its efficacy is limited in clinical practice owing to differences in the degree of effector T‐cell exhaustion. Casein kinase 2 (CK2) is a protein kinase that plays an important role in T‐cell immunity. In this study, it is aimed to explore the potential of targeting CK2 and its regulatory subunit CK2B to prevent or reverse T‐cell exhaustion, thereby enhancing the efficacy of anti‐PD‐1 therapy in NSCLC. In this study, it is found that CK2B expression is closely associated with T‐cell exhaustion as well as the efficacy of anti‐PD‐1 therapy based on scRNA‐seq and in vitro and in vivo experiments. Utilization of CK2 inhibitors or knockdown of CK2B expression can upregulate TBX21 expression through HDAC8‐mediated epigenetic reprogramming, restoring the effector function of CD8+ T cells and enhancing the efficacy of anti‐PD‐1 therapy in NSCLC. These findings underscore CK2B as a promising target for overcoming the exhaustion of effector CD8+ T cells, thereby enhancing the efficacy of anti‐PD‐1 and adoptive cell therapies in NSCLC. Moreover, CK2B expression serves as a novel predictor of immunotherapy efficacy for NSCLC.